2013
DOI: 10.1159/000355957
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Disease in Patients with Common Variable Immunodeficiency: Three Case Reports

Abstract: Common variable immunodeficiency (CVID) is the most frequent clinically relevant primary immunodeficiency and shows enormous heterogeneity in clinical presentation. Despite clinical immunodeficiency, opportunistic infections are not a typical manifestation of CVID. A retrospective study of 32 patients followed up for 335 patient-years was performed to determine the frequency of cytomegalovirus (CMV) disease. Symptomatic CMV infection was documented in 3 CVID patients. Patients No. 1 and 2 suffered from CMV pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 86 publications
2
32
0
1
Order By: Relevance
“…In general, however, the benefit of higher or more frequent dosing of IgG for viral illnesses associated with CVID is not well investigated. Multiple other factors, such as environmental (43) Adenovirus meningoencephalitis (2) [25] Bacterial meningitis (22) [1,[26][27][28][29] BKV encephalitis and optic neuritis (1) [30] CMV encephalomyelitis (1) [31] Echovirus meningoencephalitis (1) [25] Histoplasmosis (1) [28] HSV encephalitis (3) [9] Mumps encephalitis (1) Poliovirus (1) [32] Progressive Multifocal Leukoencephalopathy (6) [3][4][5][6][7][8] Toxoplasma encephalitis (2) [33,34] Varicella angiitis (1) [35] Varicella zoster encephalitis (1) [1] West Nile meningitis (1) [36] Autoimmune/Inflammatory (13) optic neuritis (1) [37] myelitis (4) [10,11,38,39] limbic encephalitis (1) [12] Guillian Barre Syndrome (1) [40] granulomatous mass (4) [41][42][43][44]45] chronic inflammatory demyelinating polyneuropathy (1) [39] acute disseminated encephalomyelitis (2) [14,46] Unknown etiology (10) encephalopathy (4...…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, the benefit of higher or more frequent dosing of IgG for viral illnesses associated with CVID is not well investigated. Multiple other factors, such as environmental (43) Adenovirus meningoencephalitis (2) [25] Bacterial meningitis (22) [1,[26][27][28][29] BKV encephalitis and optic neuritis (1) [30] CMV encephalomyelitis (1) [31] Echovirus meningoencephalitis (1) [25] Histoplasmosis (1) [28] HSV encephalitis (3) [9] Mumps encephalitis (1) Poliovirus (1) [32] Progressive Multifocal Leukoencephalopathy (6) [3][4][5][6][7][8] Toxoplasma encephalitis (2) [33,34] Varicella angiitis (1) [35] Varicella zoster encephalitis (1) [1] West Nile meningitis (1) [36] Autoimmune/Inflammatory (13) optic neuritis (1) [37] myelitis (4) [10,11,38,39] limbic encephalitis (1) [12] Guillian Barre Syndrome (1) [40] granulomatous mass (4) [41][42][43][44]45] chronic inflammatory demyelinating polyneuropathy (1) [39] acute disseminated encephalomyelitis (2) [14,46] Unknown etiology (10) encephalopathy (4...…”
Section: Discussionmentioning
confidence: 99%
“…CVID is the most common clinically significant PAD, defined by recurrent bacterial infections (and rarely by virus infections) and hypogammaglobulinemia [60,61,62,63,64]. The cellular alterations in CVID comprise a spectrum of B- and T-cell abnormalities, including defects in B-cell differentiation into plasma cell and memory B cells, defects in Treg and Breg cells, accelerated T-cell apoptosis, and abnormality in cytokine production secondary to gene polymorphisms [6,65,66,67,68].…”
Section: Autoimmunity In Padsmentioning
confidence: 99%
“…We read with interest the paper by Kralickova et al [1] on cytomegalovirus (CMV) infections in common variable immunodeficiency (CVID). We fully agree with the authors' conclusions that infections due to CMV are more frequent than previously reported.…”
Section: Figmentioning
confidence: 99%
“…In CVID patients, viral infections, such as those due to norovirus and CMV, have been reported to be of pathogenic importance in gastrointestinal (GI) damage in up to 5% of patients [2,3,4]. In the paper by Kralickova et al [1], the frequency of systemic CMV reached 10%, one third with localization in the GI tract. Information on the frequency of infectious complications of the GI tract in CVID comes mainly from one French study on 252 patients where Giardia lamblia was the predominant infectious agent, at least in patients with undetectable serum IgA levels [5].…”
Section: Figmentioning
confidence: 99%